ANALYSIS OF MODERN ERGONOMICS IN UZBEK LANGUAGE (American Journal of Research in Humanities and Social Sciences, 2023)
The article is devoted to the descriptive analysis of the units of the onomastic system. The role of source language acquisitions in the formation of names and promising ways of choosing a national name are studied on the example of ergonyms. Also, naming is a complex linguistic phenomenon, and it is considered important to take into account, first of all, the national interests of the Uzbek language, as well as the linguistic rights of national diversity in society, as well as the experience and features of naming models of world culture. This phenomenon was considered important in bringing the words of the native stock to the neim level, and the appearance of foreign language neims in such conditions was considered a natural phenomenon.